Dawâbit Al-Igtiyâl al-Ma’nawî fi al-Fiqh wa al-Qânûn al-Indûnîsî: Dirâsah Muqâranah Tahlîliyah - Imam Sujoko Sujoko; Hossam el-Dien Ibrahim el-Safy; Muntaha Artalim Zaim (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
This study purposes to analyze the issue of character assassination in perspective of Islamic Jurisprudence and Indonesia’s Law. Many people get involved in the criminal case on character assassination. Different ways in understanding and interpretating the meaning of character assassination are main problem in this article. It particularly focuses on the measurement of character assassination in Islamic Jurisprudence and Indonesia’s Law. This study is based on library research referring to books, journal articles, and official sites related to the topic. The data was then described and analyzed with the approach of Islamic Jurisprudence and Indonesia’s Law. The result of the study shows that character assassination should have measurements, as a standard of evident in which any practice of character assassination issue must be referred to. Additionally, there are some exceptional cases in which the practice of character assassination is permissible juridically and legally for Maslahah (advantage).